(untitled) - O'Kennedy, Sean James

Analysis of hydroformylation catalysis mechanisms of rhodium catalyst precursors by computational and instrumental means. (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.